Financial inclusion and inclusive growth in Africa: What is the moderation role of financial stability? - Khadijah Iddrisu; James Ntiamoah Doku; Joshua Yindenaba Abor; Raymond Dziwornu (Cogent Economics & Finance, 2023)
This article aims to explore the interplay between financial stability, financial inclusion, and inclusive growth in 40 African countries during the period 2004-2020. It acknowledges that an unstable financial system has the potential to erode confidence and hinder the essence of financial inclusion in promoting inclusive growth. However, studies regarding the combined effect of financial inclusion and financial stability on inclusive growth are hard to find, especially in Africa. By examining the effects of financial inclusion on inclusive growth and the synergistic relationship between financial stability and inclusive growth, this study seeks to shed light on how these factors interact in the context of African economies. To cater for endogeneity issues, we used a two-step system generalized method of moment. Our result reveals three outcomes: First, financial inclusion promotes inclusive growth. Second, financial stability alone is less effective to enhance inclusive growth. Lastly, financial stability forms synergy with financial inclusion to further spike inclusive growth. It is recommended that policymakers should strive to enhance financial inclusion by promoting financial stability.
Keywords: 330; Africa; financial inclusion; financial stability; inclusive growth